Poverty and Human Rights: New Direction in Poverty Eradication - Buhaerah, Pihri (Research and Development Agency Ministry of Home Affairs, 2016)
The purpose of this paper is to support the argument that poverty is multidimensional and part of human rights concern. In doing so, this paper uses relevant literature review on poverty issues. This paper finds that the capability approach is a useful conceptual framework to link conventional approach with human rights and support the argument that poverty is multidimensional. Under this perspective, there are two prerequisites cases of non-fulfillment of human rights can be counted as poverty, namely (i) the human rights involved must be those that correspond to the capabilities that are considered basic by a given society; and (ii) inadequate command over economic resources must play a role in the causal chain leading to the non-fulfillment of human rights. Furthermore, there are three different ways in which human rights can be relevant to poverty: constitutive relevance, instrumental relevance, and constraint-based relevance.